Optical coherence tomography angiography in patients with type 2 diabetes without clinical diabetic retinopathy - Omnia M Abd-Elrahman; Fatma A.E.W Atwa; Rehab M Kamel; Asmaa M Gamal (Wolters Kluwer Medknow Publications, 2021)
Background and objectives To investigate changes in retinal vascular plexuses, choriocapillaris, along with microcirculation of optic nerve head (ONH), in patients with type 2 diabetes mellitus without clinically evident retinopathy and healthy controls using optical coherence tomography angiography (OCTA). Patients and methods This is a prospective, cross-sectional observational study that included 20 eyes of normal healthy controls (group 1) and 20 eyes of diabetic patients without clinically evident retinopathy (group 2). All participants underwent OCTA examination (RTVue-XR Avanti; Optovue). Average and parafoveal vessel density in superficial capillary plexus (SCP), deep capillary plexus, choriocapillaris vessel density, foveal avascular zone area and perimeter, and vessel density inside ONH and in peripapillary region were compared between groups. Microaneurysms and capillary nonperfusion were taken into analysis. glycated hemoglobin and serum creatinine were assessed for diabetic patients. Results Group 2 showed statistically significant lower average vessel densities of SCP and deep capillary plexus (P<0.01) and parafoveal vessel density of SCP (P<0.01) compared with group 1. Moreover, there was statistically significant and highly significant difference between group 2 and group 1 regarding tempo-inferior and tempo-superior sectors of peripapillary area (P=0.016 and 0.001, respectively). A statistically significant increase in foveal avascular zone area and perimeter was found in group 2 compared with group 1 (P<0.01). Average vessel density of choriocapillaris had a negative correlation with serum creatinine in group 2 (P<0.05). Microaneurysms and capillary nonperfusion were detected by OCTA in diabetic patients. Conclusion OCTA can identify preclinical diabetic retinopathy before the clinical manifestations appear. It is a promising noninvasive tool for assessing retinal vascular plexuses, choriocapillaris, and ONH microcirculation.